Consequences Customer Satisfaction : Service Quality and Perceived Value in the Moments Of Truth - Juliana Juliana; Theresia Jessica; Monica Widodo; Jessalyn Tanubrata (LPPM Universitas BSI, 2021)
This study aims to explain the influence of service quality and perceived value on customer satisfaction at Starbucks US to understand first and second moments of truth. Consumers evaluate the quality when consumers buy an offer and when consuming it. This type of research is a quantitative study that uses the Hair theory, the sampling in this study uses a nonprobability sampling technique. The research population is 70 respondents who have been to Starbucks US as a sample of the author's study. The analysis tool uses SPSS ver 25 with a significance level of 0.05. Measurement variables, the measurement scale used in this study is the Likert scale. The results of this study can prove the hypothesis proposed by the author because it is proven that good service quality can influence customer satisfaction, and perceived value influences customer satisfaction because customers offered a good value compared to the price. So that the results of this study, it can be concluded that service quality and perceived value have a significant effect on customer satisfaction at Starbucks US.Keywords: Service Quality, Perceived Value, Customer Satisfaction